Optimal Kinematic Task Position Determination—Application and Experimental Verification for the UR-5 Manipulator - Charalampos Valsamos; Kanstantsin Miatliuk; Adam Wolniakowski; Vassilis Moulianitis; Nikos Aspragathos (Applied Sciences, 2022)
A method for determining the optimal position of a robotic task within a manipulator’s workspace considering the minimum singularity free paths in joint space in order to achieve a high kinematic performance is presented. The selected performance criterion was the minimization of the joint velocities during task execution under a given end effector velocity. The proposed method is applied to place kinematic tasks for a UR-5 manipulator. Joint speed measurements are compared for the optimal and the “bad” task positions and the results show that at the optimal position, lower joint speeds are exerted during task execution.